2019
DOI: 10.1021/acs.jproteome.9b00120
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of the Proteome and Transcriptome of the Venom of the Most Venomous European Viper: Discovery of a New Subclass of Ancestral Snake Venom Metalloproteinase Precursor-Derived Proteins

Abstract: The nose-horned viper, its nominotypical subspecies Vipera ammodytes ammodytes ( Vaa ), in particular, is, medically, one of the most relevant snakes in Europe. The local and systemic clinical manifestations of poisoning by the venom of this snake are the result of the pathophysiological effects inflicted by enzymatic and nonenzymatic venom components acting, most prominently, on the blood, cardiovascular, and nerve systems. This venom is a very complex mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 125 publications
1
34
0
Order By: Relevance
“…Gel-based proteomic analysis of the venom of the wild V. ursinii ssp. species revealed a proteome much simpler than that of the recently published V. a. ammodytes venom proteome [15]. Almost two times fewer proteins were identified in the V. ursinii ssp.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Gel-based proteomic analysis of the venom of the wild V. ursinii ssp. species revealed a proteome much simpler than that of the recently published V. a. ammodytes venom proteome [15]. Almost two times fewer proteins were identified in the V. ursinii ssp.…”
Section: Discussionmentioning
confidence: 76%
“…In vitro, VaH3 also markedly prolonged blood coagulation, due to its fibrinogenolytic activity, but only weakly affected platelet aggregation. Vaa-MPIII-1 and Vaa-MPIII-4 are present in trace amounts in the V. a. ammodytes venom [15]. In contrast, in the V. ursinii ssp.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The four subclasses (P-IIIa, b, c, and d) are well-known and documented in the literature. However, studies suggested the existence of a P-IIIe subclass comprising proteins that lack the catalytic metalloproteinase domain ( Balija et al, 2020 ; Leonardi et al, 2019 ). Although Casewell et al (2011) had previously correlated the evolutionary history of serpents to a repeated domain loss ( Casewell et al, 2011 ), recent data from proteomic and transcriptomic analysis of Vipera ammodytes ammodytes venom identified Vaa-MPIII-3 as a member of the new P-IIIe subclass ( Leonardi et al, 2019 ).…”
Section: Snake Venom Metalloproteinases (Svmps)mentioning
confidence: 99%